Hubungan antara Kelimpahan Mikroplastik dan Keanekaragaman Jenis Plankton - Astricyah, Iis; Leuwakabessy, Juliana; Toha, Abdul Hamid A. (Penerbit Brainy Bee, 2025)
This paper aims to evaluate the relationship between microplastic abundance and plankton species diversity. Microplastics, as a new and increasingly disturbing pollutant, can affect the quality of aquatic ecosystems, including plankton communities. Water samples were taken from several points in Kwatisore waters to measure microplastic concentrations, as well as to identify and count the types of plankton present. The results of the analysis will later show that there is a negative relationship between the abundance of microplastics and the diversity of plankton types. An increase in microplastic concentrations is associated with a decrease in the amount and diversity of plankton, which can impact the stability of aquatic ecosystems. These findings underscore the importance of managing and mitigating plastic pollution to maintain healthy aquatic ecosystems. Further research is needed to understand the impact mechanisms of microplastics in more depth and to develop effective conservation strategies.